Vancomycin-Induced Stevens-Johnson Syndrome in a Boy Under 2 Years Old: An Early Diagnosis by Granulysin Rapid Test - Lin, You-Cheng; Sheu, Ji-Nan; Chung, Wen-Hung; Pan, Ren-You; Hung, Chu-Ju; Cheng, Jen-Jung; Hsiao, Yu-Ping (Frontiers in Pediatrics, 2018)
Stevens-Johnson syndrome (SJS) is a life-threatening disease which is mainly ascribed to drugs, such as sulfonamides and psychoepileptics. In this article, we present a pediatric case of vancomycin-induced SJS and an alternative diagnostic algorithm. The patient presented with multiple target-like rashes and vesicles throughout the whole body after receiving vancomycin. Despite the fact that skin biopsy remains the gold standard for diagnosing SJS, the granulysin rapid test by immunochromatographic assay is a non-invasive option for children. In this article, we describe our use of the Algorithm of Drug causality for Epidermal Necrolysis and a modified T-cell activation assay for granzyme B and Interferon Gamma to screen for the culprit drug. Moreover, we applied the granulysin rapid test as an early diagnosis method for children with drug-induced SJS.